2000-2010, dix ans d’histoire de la plaine inondable de la Gloriette, à Tours - Bruno Marmiroli (Projets de Paysage)
The plain of the Gloriette, in Tours, served between 2000 and 2010, as a testing ground for garden projects driven by the municipality. The building of facilities, their methods of design and management, have been a fantastic opportunity to test the marginal process of production of forms in a flood area. Over the years, a special relationship between landscape designers and the owners has lead to the formation of production teams beyond the traditional relationship conditioned by the procurement code. The study of these 10 years of practice and relations sheds light on the difficulties of implementing landscape projects in the legal frameworks imposed for municipalities, landscape designers and contractors.